Simultaneous or staged lateral ridge augmentation: A clinical guideline on the decision‐making process - Yu, Shan‐Huey; Saleh, Muhammad H. A.; Wang, Hom‐Lay (Periodontology 2000, 2023)
Lateral ridge augmentation is a standard surgical procedure that can be performed prior to (staged) or simultaneously with implant placement. The decision between a simultaneous or staged approach involves considering multiple variables. This paper proposed a decision‐making process that serves as a guideline for choosing the best treatment choice based on the available evidence and the author's clinical experience.